Assessing the effectiveness of preventing placenta-associated complications in patients with burdened obstetric history and circulating antiphospholipid antibodies - D. R. Eremeeva; M. S. Zainulina (IRBIS LLC, 2024)
Introduction. The role of antiphospholipid antibody (APA) carriage in the pathogenesis of pregnancy failure is one of the most recently debated issues. To date, no unified therapeutic approach to immunotherapy of antiphospholipid syndrome (APS) in pregnancy exists. Intravenous immunoglobulins (IVIG) have become the drugs of choice to treat this pathology in pregnant women.Aim: to evaluate an effectiveness of preventing placenta-associated complications (PACs) in patients with recurrent miscarriage and circulating APAs.Materials and Methods. A prospective study was conducted to analyze the course of pregnancy and outcomes in 150 patients who had diagnostic APA titers and aggravated obstetric and gynecological anamnesis. All pregnant women received therapy with low-dose aspirin (LDA) and low molecular weight heparin (LMWHs). In addition to combining LMWHs and LDA, 126 (84.0 %) pregnant women received IVIG courses administered at gestational age of 6-8, 12-14, and 22-24 weeks.Results. Based on the data obtained, gestational complications such as chronic placental insufficiency, hemodynamic disorders, fetal growth retardation, gestational arterial hypertension, moderate preeclampsia (PE) were significantly more frequent in patients receiving no IVIG during pregnancy. It should be noted that development of severe obstetric complications, such as severe PE, premature detachment of a normally located placenta, massive blood loss, and antenatal fetal death were not observed in any case. No patient developed venous thromboembolism during pregnancy and in the postpartum period. Comparing relative expression area of annexin V, CD 34+, KiSS-peptine and its receptors (KiSS1R), there were revealed significant differences. The relative expression area for anticoagulant protein annexin V was 2.3-fold higher in IVIG-treated patients in pregnancy; endothelial marker CD34+ - 4-fold higher, KiSS-peptine - 2.3-fold higher, and KiSS1R - 5.4-fold higher in placenta from women treated with IVIG starting from early pregnancy stage.Conclusion. In order to assess the effectiveness of PAC prevention in patients with habitual miscarriage and circulating APAs, it is possible to estimate relative expression area for placental anticoagulant protein annexin V, endothelial marker CD 34+, KiSS-peptine and KiSS1R.